The well-being of Polish general practitioners during the COVID-19 pandemic-cross-sectional questionnaire-based study - Katarzyna Nessler; Krzysztof Studziński; Esther Van Poel; Sara Willems; Ewa Wójtowicz; Elżbieta Kryj – Radziszewska; Adam Windak (BMC Primary Care)
Abstract Background The COVID-19 pandemic has caused psychological distress to the population and healthcare workers. Physicians’ well-being is essential and contributes significantly to overall health. This study aimed to assess the strain on Polish general practitioners from the effects of the COVID-19 pandemic and to ascertain the potential predictors of their distress. Methods Data was collected using a self-reported online questionnaire from 162 GPs in Poland between December 2020 and August 2021 as part of the international PRICOV-19 study. General practitioners’ well-being was evaluated using the validated Mayo Clinic’s expanded 9-item well-being index (eWBI). Spearman’s correlation was used to measure the strength and direction of association between general practitioners’ distress level and continuous variables, and for ordinal variables, Gamma correlation was recommended for many tide ranks. We also checked the association of the level of distress with continuous variables by categorizing them and applying the Kruskal-Wallis test likewise for a comparison of the distress in different practice locations. Results A vast majority (80%) of respondents were considered at risk of distress during the COVID-19 outbreak, with an eWBI score of 2 or more. Higher distress scores were exhibited among general practitioners who reported increased responsibilities during the COVID-19 pandemic and perceived need for additional training. The experience of collaboration with neighbouring practices and the provision of adequate governmental support emerged as significant protective factors against distress. No correlation was observed between Polish general practitioners’ distress level and years of professional experience, number of patients in the practice, number of doctors working there, the practice’s location, or working with more vulnerable patient populations. Conclusions Our findings proved that COVID-19 placed an extraordinary emotional burden on Polish general practitioners and highlighted the importance of targeted support services and resource allocation to primary healthcare in Poland in case of any potential future crisis similar to the COVID-19 pandemic.